Pengaruh System Arus Kas, Pengendalian Internal Dan Struktur Modal Terhadap Kinerja Keuangan Dengan Ukuran Perusahaan Sebagaivariabel Moderating Pada Perusahaan Property Dan Real Estate Yang Terdaftar Dibursa Efek Indonesia Periode 2020- 2024 - Sari Desri Zulianty; Berta Agus Petra; Devi Edriani (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to analyze the influence of cash flow systems, internal control, and capital structure on financial performance, with company size as a moderating variable. The study was conducted on property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. Purposive sampling was used to select 15 companies from a population of 92. The data were analyzed using panel data regression analysis. The results indicate that cash flow systems have a significant partial effect on financial performance, while internal control has no significant partial effect on financial performance. Capital structure, while moderated by company size, has no significant effect on financial performance.